Understanding wisdom literature: conflict and dissonance in the Hebrew text - Penchansky, David (Eerdmans, 2012)
Who are the sages? -- What unity in Proverbs? -- The meaning of the Book of Job -- Wisdom, madness, and folly : the three qoheleths -- Sounds of silence : the absence of covenantal theology in the wisdom literature -- Sophia and Simon : the two poles of Ben Sira's affection -- The conservatism of Pseudo-Solomon